ROLE OF PHYSIOLOGICAL AND ANTIOXIDATIVE ENZYMES IN IMPROVING UNDER DROUGHT STRESS CONDITIONS IN CLUSTER BEAN [CYAMOPSISTETRAGONOLOBA(L.) TAUB]. - Ragula Seenaiah1*, Pinjari Akbar Basha2, Metla Jyothi3, Subba Naik Gari Thimma Naik4, (Chelonian Research Foundation, 2023)
Cluster bean [Cyamopsistetragonoloba(L.) Taub, member of the Fabaceae family and drought tolerant plant. The drought stress that occurs during pod filling stage is critical for final pod and fodder yield of cluster bean. The importance of the yield loss, both in terms of quality and quantity would usually depend on the response of cluster bean varieties to drought stress. This provided a detailed description of an experiment or study on the impact of water stress on chlorophyll content, cell membrane injury, and various biochemical parameters in different cultivars of cluster bean genotypes. The percent decrease in total chlorophyll content was higher in certain drought-sensitive genotypes (RGC-936, RGC-1025, HG-365) compared to drought-tolerant genotypes (JG-2, JG-1, GLC-103) at low soil moisture. Membrane injury increased significantly with the intensity of water stress in both cultivars. Drought-tolerant genotypes (RGC-936, RGC-1025, HG-365) exhibited a lower percent membrane injury compared to drought-sensitive genotypes (JG-2, JG-1, GLC-1031) under severe stress. Free proline and proline significantly increased in all genotypes with increasing stress. Antioxidative Enzymes, Superoxide Dismutase (SOD), Catalase (CAT), Glutathione Reductase (GR ) SOD activity increased in both cultivars under water stress, with a higher increase in drought-tolerant genotypes at low soil moisture. Key Words: Cluster bean, drought stress, Membrane injury, Antioxidative Enzymes